Evolution of Orthodontic Aligners – A Narrative Review - Trupti Shankar Nakhate; Suresh Kangane; YatishKumar S Joshi; Payal Brijlal Bhutada; Swathilekshmi Nair; Aavesh Dnyaneshwar Bhoir (Dentistry and Medical Research)
Clear aligners seem to be a new modality for patients undergoing orthodontic treatment; the initial concept of this treatment evolved in the 20th century. Remensnyder’s “Flex-O-Tite” appliance led to the introduction of the aligner, from this Kesling tooth positioner appliance made up of rubber-based 1945 proposed the concept of using it for minor tooth movements in a sequential series. The purpose of this article is to provide information about the chronologically ordered evolution of aligners. Various types of generations and attachments are used in different aligner systems. An online search was done using databases from PubMed and Google Scholar to find the articles. Database search was done with the following string: ((aligners [Title/Abstract]) AND (comparison [Title/Abstract])) AND (((fixed appliance [Title/Abstract]) OR (braces [Title/Abstract])) OR (fixed orthodontic appliance [Title/Abstract])). Three articles are included in the narrative review to evaluate the better outcomes of the treatment effectiveness between fixed orthodontic treatment and aligners with a short summary of chronologically ordered evolution, generations, and attachments of aligners. The overall effectiveness of orthodontic treatment depends upon the knowledge of the clinician, therefore, knowledge about recent advances is important for proper treatment of the patient.